The Vibrio Cholera - Sataaar, Jaafer (Journal of the Faculty of Medicine Baghdad, 2008)
Introduction:Vibrios are gram negative rods bacteria that are all widely distributed in nature the vibrose are found in marine and surface waters. They are curved aerobic rodsand are motile, possessing a polar flagellum. V.vibrios sero group 01 and related Vibrios cause cholera cause sepsis or enteritis Vibrio cholerae The epidemiologyof cholera closely parallels the recognition of V.cholerae transmission in water and the development of sanitary water system (1,2,6,9). V. C is a comma-shaped, curved rod 2-4 long .It is actively motile by means of polar flagellu on prolonged cultivation. Vibros may become straight rod that  resemble the gram-negative enteric bacteria (1,2,6,9). V.C. grow well at 37OC on many kinds of media .including defined media containing mineral salt sand asparagines as sources of carbon and nitrogen V. C. produce convex, smooth round colonies that are opaque and granular in transmitted light V.C. grows well on thiosulfate-citrate yellow colonies . V. are oxidasepositive, vibrio grow at Avery high Pi-Land are rapidly killed by acid (1,2,3,6).V.C. and related produce a heat-lebile entero toxin with molecular weight of about 84,000 consisting of subunits A and B .The genes for V.C. enterotoxin are on the bacterial chromosome-cholera enterotoxin is antigenincally related to LT of E-coli and can stimulate the production of neutralizing antibodies .However, the precise role of antitoxic and antibodies in protection against cholera is not clear. (3,6) Its structure was determined with one and two dimensional NMR spectra (COSY, HMBC, HMQC, HOHAHA on nuclei 1H, 13C and 31P) and was furtherconfirmed with HPLC (18).